Paradigma Pendidikan Islam Holistik - M. Zainuddin (Ulumuna, 2011)
M. Zainuddin There is a number of Islamic Education outputs who could not meet the needs of society and the development of science and technology. Therefore, a wholistic paradigm of Islamic education which urgently needs to be formulated and applied in Islamic education This article focuses on how Islamic education does not only cover eschatological dimension, but also profane one. The approach or methodology used in this paper is a philosophical one. The results of the study recommend that the concept and curriculum of Islamic education should be focused on character building and values teaching as well as developing skills of communication, interpersonal relationships, community service, and leadership which all support the actualization of human duties and responsibilities as God’s khalîfah on the earth.